P456 Ig glycosylation in ulcerative colitis: it's time for new biomarkers. (27th May 2021) - Capecchi, R; Migliorini, P; Zanzi, F; Maltinti, S; Puxeddu, I; De Bortoli, N; Bellini, M; Costa, F; Marchi, S; Bertani, L
Abstract: Background: Ulcerative colitis (UC) is a chronic relapsing disease, which needs a continue monitoring, especially during biological therapies. An increasing number of patients is treated with anti-Tumor Necrosis factor (TNF) drugs, and current research is focalized to identify biomarkers able to monitor the disease and to predict therapeutic outcome. Methods: We enrolled consecutive UC patients treated with anti-TNF, naïve to biologic drugs. Therapeutic outcome was evaluated after 54 weeks of treatment in terms of clinical remission (Partial Mayo Score -PMS- <2) and mucosal healing (Mayo Endoscopic Score <2). On serum samples collected at baseline and after 54 weeks of treatment, a Lectin-based ELISA assay was performed, and specific glycosylation patterns were evaluated by biotin-labelled lectins. We have also collected 21 healthy controls (NHS) samples, age and sex-matched. Results: Out of 44 UC patients enrolled, 22 achieved clinical remission and mucosal healing after 54 weeks. At baseline, when Protein A was used as coating, UC patients non-responders showed a reduced reactivity to Jacalin (JAC) in comparison with NHS (p=0, 04). After one year of treatment, a decrease in JAC binding was seen only in responders, in comparison with baseline (p=0, 04). When JAC binding was tested selecting IgG by means of Fab anti-IgG Fab, UC patients displayed an increased reactivity after anti-TNF therapy (p<0, 0001 vs controls). At baseline, PMS inversely correlates with JAC binding when Fab anti-IgG Fab was used in solid phase (r2= 0, 2211; p=0, 0033). Patients with higher PMS at baseline (PMS ≥5) presented lower binding capacity for JAC in comparison with NHS and with lower PMS patients (p= 0, 0135 and p=0, 0089, respectively). Conclusion: Ig glycosylation was correlated with clinical and endoscopic activity in patients with UC. JAC protein A-selected Ig showed a possible role in predicting therapeutic effectiveness. If these data would be confirmed, Ig glycosylation could be used as biomarker in UC.